Features of Conclusion of Electronic Transactions Requiring a Notarial Certificate - Khomenko, Viktoriia O.; Krukevych, Oksana M.; Hetmantsev, Maksym O.; Opanashuk, Yurii Yu. (International Journal of Criminology and Sociology, 2021)
The urgency and urgent necessity to develop a research topic are due to a number of factors. First of all, the legal community unanimously reached a consensus on the necessity to reform the institution of notaries in the direction of expanding the powers and functions of public and private notaries, increasing the requirements for these participants in the context of the procedure of certification of transactions (contracts) in various fields. The reform of the Ukrainian notary has recently exhausted its potential and positive expectations on the part of civil society, which is only complicated by the progressive situation with the spread of acute respiratory infections caused by the COVID-19 SARS-CoV-2 virus. The purpose of this article was to objectively outline the existing problems in the field of law enforcement, related to the peculiarities of electronic transactions that require notarization, with the formulation of author’s proposals to improve legislation in this area. The study was conducted using a number of general and special methods, a key role among which was played by comparative legal and statistical-prognostic methods, which were used to thoroughly analyze the current state of affairs in the field of electronic certification of transactions by notaries. As a result of the study, the authors concluded that in the development of the global information society and digital economy, the issue of electronic transactions requiring notarization needs further involvement of both theoretical and scientific research, as well as the development of practical solutions and proposals to improve the electronic interaction system.